2010
DOI: 10.1093/annonc/mdp568
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of TNF-α and IL-6 predict the clinical outcome of treatment with human recombinant erythropoietin in anaemic cancer patients

Abstract: High serum levels of TNF-alpha and IL-6 at the baseline are significantly correlated with a negative response to administration with rHuEPO. Thus, pretreatment evaluation of TNF-alpha and IL-6 serum levels can help to select those patients who are most likely to benefit from treatment with rHuEPO. On the contrary, Hb level, red blood cell count, lactate dehydrogenase and BFI score do not predict the outcome of treatment with rHuEPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“… Peak circulating levels (mean ± SEM) of IL‐6 or TNF‐α in response to fever or various moderate‐to‐severe inflammatory states . The IL‐6 and TNF‐α concentrations in cancer patients and in healthy subjects were obtained by compiling data from multiple references and calculating pooled standard deviations taking into account the different number of subjects, n , between trials.…”
Section: Markers Of Decreased Drug Clearance (Ie Acute Phase Reactmentioning
confidence: 99%
“… Peak circulating levels (mean ± SEM) of IL‐6 or TNF‐α in response to fever or various moderate‐to‐severe inflammatory states . The IL‐6 and TNF‐α concentrations in cancer patients and in healthy subjects were obtained by compiling data from multiple references and calculating pooled standard deviations taking into account the different number of subjects, n , between trials.…”
Section: Markers Of Decreased Drug Clearance (Ie Acute Phase Reactmentioning
confidence: 99%
“…This decrease in the levels of the proinflammatory cytokines, particularly IL-6, may explain the decreases in hepcidin levels observed in EPO-treated subjects. Pavese et al [44] demonstrated that, in ESA-hyporesponsive cancer patients, high baseline serum levels of TNF-α and IL-6 were significantly correlated with a negative response to ESA. This may be attributed to the fact that profound and persistent inflammation, which may not be overcome by ESA administration, may decrease hepcidin levels and account for the reduced response to ESA treatment.…”
Section: Causal Role Of Hepcidin In Anemia Of Inflammation and Effectmentioning
confidence: 99%
“…Also, a fine Th1/Th2 immunity imbalance affects the IL-10/IL-12 regulatory circuit [14, 53, 54] and leads to over expression of IL-12 and TNF- α cytokines in patients with chronic fatigue. An increase of circulating TNF- α levels has been associated with significant fatigue in cholestatic patients with cancer [55]. Finally, work on animal models of chronic fatigue syndrome has also underlined the important pathogenic role of TRAF1-related cytokines, such as TNF α [32, 34].…”
Section: Discussionmentioning
confidence: 99%